The power of kings : monarchy and religion in Europe, 1589-1715 - Monod, Paul Kléber (Yale University Press, 1999)
"Discussing monarchies throughout Europe, from Britain to Russia, Monod tells how sixteenth-century kings and queens were thought to heal the sick with a touch, were mediators between divine authority and the Christian self in quasi-religious ceremonies, and were seen as ideal mirrors of human identity. By 1715, the sacred authority of the monarchy had been supplanted by an ideology fusing internal moral responsibility with external obedience to an abstract political authority. Subjects were expected to identify not with a sacred king but with the natural person of the ruler. No longer divine, the kings and queens of the Enlightenment took up a new, more human place in the hearts and minds of their subjects."--Jacket.